Homo migrans. Miejsce literatury dla dzieci i młodzieży w edukacji empatii - Małgorzata Wójcik-Dudek (Postscriptum Polonistyczne)
The paper is an attempt to present the ways of functioning of the migration issue in the latest Polish literature for children and young people, which uses a certain universal topos, namely the home and narratives related to hospitality, when presenting the phenomenon studied. Such a problematised view of the issue is inscribed in the reflection on intercultural education, under the patronage of the philosophy of love and compassion represented by Martha Nussbaum. The assumptions of the humanistic philosophy of love will be confronted with the (pre-)school and school practice preparing children to meet the Other.